Open source automated insulin delivery systems: benefits, limitations and challenges in diabetes care - K. S. Shishin; V. V. Klimontov (Сахарный диабет)
Open source closed loop automated insulin delivery (CL-AID) systems are increasingly used in the treatment of diabetes. Assembled on a do-it-yourself (DIY) basis, these systems integrate insulin pumps, continuous glucose monitoring devices, and algorithms that control the rate of insulin delivery based on glucose levels. In this review, we consider the technological features of open source CL-AID systems (OpenAPS, AndroidAPS, Loop, etc.), advantages and barriers to their use in clinical practice. Advantages of open source CL-AID systems over commercially available ones included lower cost, a choice of devices, a wide range of user settings, as well as continuous improvement of algorithms. A growing body of evidence indicates that open source CL-AID systems, such as OpenAPS, AndroidAPS, and Loop, provide an excellent time in range with minimal risk of hypoglycaemia and increase treatment satisfaction in patients with type 1 diabetes. A wide range of settings makes open source systems an effective tool for managing diabetes in situations with rapidly changing insulin requirement. However, some technological, medical, legal and ethical issues associated with the use of non-commercial CL-AID systems still need to be addressed. Assembling the system requires skills in diabetes technology. The issue of cybersecurity is also relevant. Lack of official approvals, low awareness of medical professionals, and reimbursement issues are slowing down the introduction of the technology into clinical practice. The professional medical community at the international and national levels needs to determine its position regarding the use of open source CL-AID systems in the treatment of diabetes.